An assessment and reformulation of the mission statement of Colegio De La Purisima Conception, Roxas City - Fungot, Clemente F. (Animo Repository, 1993)
This study aims to assess the mission statement of Colegio de la Purisima Concepcion (CPC) and to investigate the extent to which the institutional objectives of the college were realized, as bases for the reformulation of its mission statement. The historical and descriptive survey procedures were employed in the study. The primary instruments used to gather the needed data were: (1) Mission Statement Evaluation Questionnaire (MSEQ) and (2) Goals Statement Inventory (GSI). The Mission Statement Evaluation Questionnaire was used to evaluate the CPC mission statement on the bases of three dimensions, namely structure, content and style. The extent to which the institutional goals were realized was measured by the Goals Statement Inventory (GSI). The evaluation centered on ten dimensions: academic development, individual personal development, Christian formation, community service, democratic governance, freedom dimension, national consciousness, economic self-sufficiency, institutional esprit and innovative change. There were 325 respondents categorized into six groups: Board of Trustees/Administrators (25), faculty (70), support personnel (50), students (90), alumni (40) and parents (50). Their responses to the GSI were used in determining the extent to which the goals were realized. Data gathering took place during the school year 1992-1993. Based on the findings of the study, the following conclusions were drawn: 1. The CPC mission statement needed reformulation to meet present-day needs. 2. The assessment results revealed the aspects of the mission statement that needed improvement. It also showed the extent of involvement of the Board of Trustees in the operations of CPC. 3. The mission statement is an important document that ensures the existence of an educational institution. 4. An assessment of the mission statement and goals of an educational institution provides direction to the aspects that needed to be developed and strengthened. It stimulates awareness of the desirable goals which the academic community perceives to be substantially realized. 5. The participative approach of mission statement reformulation where the Board of Trustees, Administrators, faculty, non-teaching personnel, students, alumni and parents are involved leads to a consensus among the stakeholders regarding desired institutional goals and values. This may insure acceptance and owning of the mission statement and institutional goals by the academic community.